The role of Muslim preachers in Europe. The case of Tariq Ramadan. - Mohsen-Finan, Khadija Mohsen-Finan (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article introduces the reader to the case of Tariq Ramadan, a religious leader of Islam. He is one example of the new religious «Islamic intellectuals» who have emerged in the past ten years. «Islamic intellectuals» are different from the traditional imam; one of their characteristics is their solid intellectual background. Their aptitudes make them leaders in the integration of young Muslims in the European context. These Islamic intellectuals promote a humanitarian Islamism that emphasises spiritual and ethical aspects together with a citizen commitment.